Carbon dioxide corrosion resistant cement paste and preparation method thereof

By using a combination of nanoparticle filler and sheet filler in cement slurry, the irregular pore structure in cement stone is filled, and the problem of insufficient corrosion resistance of existing cement slurry in high temperature and high carbon dioxide environment is solved, and the efficient corrosion resistance and mechanical strength of cement stone is achieved.

CN120229912APending Publication Date: 2025-07-01CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410000025.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-01
Publication Date
2025-07-01

AI Technical Summary

Technical Problem

The existing cement slurry has insufficient corrosion resistance in high temperature and high carbon dioxide environments, and cannot effectively prevent the corrosion of carbon dioxide on the cement ring.

Method used

By combining nanoparticle filler and sheet filler, the irregular pore structure in cement stone is filled with the corrosion resistance of cement stone by adjusting the mass ratio of nanoparticle filler and sheet filler.

Benefits of technology

The corrosion resistance and mechanical strength of cement stone formed after cement slurry is significantly improved, ensuring the long-term sealing integrity of cement rings under high temperature and high carbon dioxide environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004643659260000091
    Figure BDA0004643659260000091
Patent Text Reader

Abstract

The invention relates to the technical field of oil and gas well cementing cement paste, in particular to carbon dioxide corrosion resistant cement paste and a preparation method thereof. Wherein the cement paste is prepared from the following preparation raw materials in parts by weight: 800 parts of cement, 40 to 80 parts of nano-particle filler, 2 to 15 parts of flaky filler, 1 to 10 parts of surfactant, 1 to 8 parts of defoaming agent, 20 to 50 parts of fluid loss agent, 0.5 to 5.5 parts of dispersing agent, 0.5 to 6.5 parts of retarder and 200 to 500 parts of water. The carbon dioxide corrosion resistant cement paste provided by the invention not only can significantly improve the corrosion resistance of set cement formed after the cement paste is cured, but also can help to improve the mechanical strength of the set cement to oil and gas wells and improve the sealing capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of oil and gas well cement slurries, and specifically relates to a cement slurry resistant to carbon dioxide corrosion and a preparation method thereof. Background Art

[0002] There are more and more oil and gas wells containing carbon dioxide. Preventing carbon dioxide from corroding the cement sheath of the well is an issue that has to be faced in the safe and efficient development of oil and gas fields. The cement sheath is a ring-shaped cement stone formed after the cement slurry solidifies. At present, the main methods to improve the carbon dioxide corrosion resistance of the cement stone are to add polymer preservatives or filler-type powder preservatives to the cement slurry. Polymer preservatives mainly achieve the anti-corrosion effect by adsorbing on the surface of the substrate to form an organic film to hinder the influence of corrosive media on the matrix of the cement sheath. However, when it is applied at a relatively high temperature, its stability is difficult to guarantee, and the polymer foaming effect is obvious. If used improperly, it is likely to have a harmful effect on the cement sheath.

[0003] Filler-type powder preservatives mainly fill the internal pores of the cement stone by virtue of their small particle size, and resist carbon dioxide corrosion by improving the density of the cement stone and reducing the permeability of the cement stone. However, the pores in the cement stone formed by the curing of oil well cement slurry are extremely small, usually in the nano-micron range, and the internal pore structure of the cement stone is in various irregular shapes. Conventional spherical anti-corrosion filler materials cannot effectively fill them. In addition, the powder-like preservatives are prone to agglomeration in the system, and there are also problems of uneven dispersion.

[0004] CN115043621A discloses a high-temperature resistant and carbon dioxide corrosion resistant high-density cement slurry and its preparation method and application. By weight, it includes the following preparation raw materials: 100 parts of cement; 6 - 12 parts of fluid loss reducer; 4 - 9 parts of dispersant; 5 - 8 parts of retarder; 35 - 40 parts of high-temperature stabilizer, and the high-temperature stabilizer is silica sand; 20 - 40 parts of high-temperature preservative, and the high-temperature preservative is one or more of microsilica, slag, basic zinc carbonate, calcium silicate and latex powder; 50 - 240 parts of weighting agent; 56 - 80 parts of fresh water. This cement slurry has strong high-temperature resistance, its density can be adjusted within a large range, and its carbon dioxide corrosion resistance is excellent. However, most of the filling materials of this cement slurry are in the micron range and cannot fill the nano-level pores in the cement stone, and the carbon dioxide corrosion resistance of the cement stone still needs to be further improved.

[0005] Therefore, for complex formations with carbon dioxide acidic gas, it is urgent to develop a cement slurry with excellent carbon dioxide corrosion resistance. Summary of the Invention

[0006] The purpose of the present invention is to overcome the problem of poor carbon dioxide corrosion resistance of the cement stone existing in the prior art, and provide a cement slurry resistant to carbon dioxide corrosion and a preparation method thereof.

[0007] To achieve the above object, a first aspect of the present invention provides a cement slurry resistant to carbon dioxide corrosion. Among them, by weight, the cement slurry comprises the following preparation raw materials: 800 parts of cement, 40 - 80 parts of nano-particle filler, 2 - 15 parts of flaky filler, 1 - 10 parts of surfactant, 1 - 8 parts of defoamer, 20 - 50 parts of fluid loss reducer, 0.5 - 5.5 parts of dispersant, 0.5 - 6.5 parts of retarder, and 200 - 500 parts of water.

[0008] A second aspect of the present invention provides a preparation method of the cement slurry described in the first aspect of the present invention; wherein, the method comprises: mixing cement, nano-particle filler, flaky filler, surfactant, defoamer, fluid loss reducer, dispersant, retarder with water to obtain the cement slurry.

[0009] Through the above technical solutions, the beneficial technical effects obtained by the present invention are as follows:

[0010] 1) In the cement slurry resistant to carbon dioxide corrosion provided by the present invention, the nano-particle filler and the flaky filler interact with each other, which can not only significantly improve the corrosion resistance of the cement stone formed after the cement slurry is cured, but also help to improve the sealing ability of the cement stone to the oil and gas well;

[0011] 2) In the cement slurry resistant to carbon dioxide corrosion provided by the present invention, the surfactant and the defoamer act synergistically, which helps to further improve the mechanical strength of the cement stone;

[0012] 3) The preparation method of the cement slurry resistant to carbon dioxide corrosion provided by the present invention is simple in operation and suitable for industrial promotion. Specific Embodiments

[0013] The endpoints and any values disclosed in the ranges in this article are not limited to the exact ranges or values. These ranges or values should be understood to include values close to these ranges or values. For numerical ranges, between the endpoint values of each range, between the endpoint values of each range and a single point value, and between single point values, they can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0014] A first aspect of the present invention provides a cement slurry resistant to carbon dioxide corrosion. Among them, by weight, the cement slurry comprises the following preparation raw materials: 800 parts of cement, 40 - 80 parts of nano-particle filler, 2 - 15 parts of flaky filler, 1 - 10 parts of surfactant, 1 - 8 parts of defoamer, 20 - 50 parts of fluid loss reducer, 0.5 - 5.5 parts of dispersant, 0.5 - 6.5 parts of retarder, and 200 - 500 parts of water.

[0015] Among them, in the present invention, the synergistic action of specific contents of cement, nano-particle filler, flaky filler, surfactant, defoamer, fluid loss reducer, dispersant, retarder and water can enable the cement stone formed after the cement slurry is solidified to have the advantages of low permeability, good stability, high compressive strength and strong carbon dioxide corrosion resistance.

[0016] In a preferred embodiment of the present invention, by weight, the cement slurry comprises the following preparation raw materials: 800 parts of cement, 50-70 parts of nano-particle filler, 6-10 parts of flaky filler, 4-6 parts of surfactant, 4-6 parts of defoamer, 30-40 parts of fluid loss reducer, 2-4 parts of dispersant, 1-3 parts of retarder and 300-400 parts of water.

[0017] Among them, in the present invention, when the dosages of cement, nano-particle filler, flaky filler, surfactant, defoamer, fluid loss reducer, dispersant, retarder and water are within the above-defined ranges, the comprehensive performance of the cement stone formed after the cement slurry is solidified is better.

[0018] In a preferred embodiment of the present invention, the cement is G-class oil well cement. Among them, the present invention does not make special limitations on the cement, and common oil well cements in the art can be used in the present invention.

[0019] In a preferred embodiment of the present invention, the particle size of the nano-particle filler is 1-100 nm, preferably 30-60 nm; the thickness of the flaky filler is 1-120 nm, preferably 1-50 nm; the average particle size is 0.1-10 μm, preferably 0.2-1 μm.

[0020] Among them, in the present invention, the nano-particle filler and the flaky filler interact with each other. On the one hand, it can reduce the permeability of the cement stone, prevent the cement stone from being corroded by acidic gases, and improve the corrosion resistance of the cement slurry; on the other hand, it can promote the hydration of the cement slurry and enhance the high compressive strength of the cement stone.

[0021] In a preferred embodiment of the present invention, the nano-particle filler is selected from one or more of nano-silica, nano-zirconia, nano-calcium carbonate, nano-titanium dioxide, nano-zinc oxide, and is preferably nano-silica.

[0022] In a preferred embodiment of the present invention, the flaky filler is selected from one or more of flaky graphene, flaky boron nitride, flaky montmorillonite, flaky molybdenum disulfide, and is preferably flaky graphene.

[0023] In a preferred embodiment of the present invention, the mass ratio of the nano-particle filler to the flaky filler is 0.5-3.5:1, preferably 1-2.5:1.

[0024] Among them, in the present invention, by adjusting the mass ratio of the nanoparticle filler and the flaky filler, the irregular pore structure in the cement stone can be better filled, and the strength and anti-corrosion performance of the cement stone can be further improved.

[0025] In a preferred embodiment of the present invention, the surfactant is selected from one or more of sodium dodecyl sulfate, sodium dodecylbenzenesulfonate, sodium glycocholate, fatty acid glyceride, sorbitan fatty acid ester, and polysorbate (Polysorbate-80), and preferably sodium dodecyl sulfate.

[0026] In a preferred embodiment of the present invention, the defoamer is a polyether defoamer. For example, SWX-1 defoamer produced by Tianjin Zhongyou Boxstar Engineering Technology Co., Ltd., XP-1 defoamer produced by Weihui Chemical Industry Co., Ltd., and DZX-1 produced by Dezhou Continental Shelf Petroleum Engineering Technology Co., Ltd.

[0027] Among them, in the present invention, the defoamer and the surfactant act synergistically, which helps to improve the stability of the cement slurry, prevent the precipitation of solid particles, minimize the density difference between the upper and lower parts of the cement stone as much as possible, avoid the cracking of the cement stone caused by poor local pressure-bearing capacity, and contribute to further improving the strength of the cement stone.

[0028] In a preferred embodiment of the present invention, the fluid loss reducer is selected from one or more of hydrolyzed polyacrylonitrile, carboxymethyl hydroxyethyl cellulose, and 2-acrylamide-2-methylpropanesulfonic acid-acrylic acid-acrylamide triblock copolymer, and preferably 2-acrylamide-2-methylpropanesulfonic acid-acrylic acid-acrylamide triblock copolymer.

[0029] In a preferred embodiment of the present invention, the dispersant is selected from one or more of formaldehyde acetone condensate, styrene-maleic anhydride copolymer, and polynaphthalenesulfonate, and preferably formaldehyde acetone condensate.

[0030] In a preferred embodiment of the present invention, the retarder is selected from one or more of sodium ethylene diamine tetra (methylene phosphonate), sodium borate, and 2-acrylamido-2-methylpropanesulfonic acid / itaconic acid binary copolymer, and preferably 2-acrylamido-2-methylpropanesulfonic acid / itaconic acid binary copolymer.

[0031] Among them, in the present invention, the fluid loss reducer, the dispersant, and the retarder are all conventional additives in the art, and the present invention does not make special limitations on them.

[0032] In a preferred embodiment of the present invention, the salt content of the water ≤ 0.5 g / L, preferably 0.2 - 0.5 g / L.

[0033] Among them, in the present invention, the cement slurry provided in the present invention for resisting carbon dioxide corrosion may further include some common additives in the art, such as weighting agents, lubricants, preservatives, stabilizers, and so on. The specific types and amounts of additives can be selected according to the actual situation, and will not be elaborated one by one in the present invention.

[0034] The second aspect of the present invention provides a preparation method of the cement slurry described in the first aspect of the present invention, wherein the method includes: mixing cement, nano-particle filler, flaky filler, surfactant, defoamer, fluid loss reducer, dispersant, retarder and water to obtain the cement slurry.

[0035] In a preferred embodiment of the present invention, the method includes the following steps:

[0036] (1) Mix the nano-particle filler, flaky filler, surfactant and water evenly to obtain a dispersion liquid;

[0037] (2) Mix the fluid loss reducer, dispersant, retarder, defoamer and the dispersion liquid evenly to obtain a mixed liquid;

[0038] (3) Add the cement into the mixed liquid and mix evenly to obtain the cement slurry for resisting carbon dioxide corrosion.

[0039] In a preferred embodiment of the present invention, after mixing the nano-particle filler, flaky filler, surfactant and water, ultrasonic treatment is carried out to obtain a dispersion liquid; wherein, the ultrasonic treatment time is 20 - 40 min.

[0040] In a preferred embodiment of the present invention, the cement is added into the mixed liquid under the condition that the stirring rate is 3500 - 4500 r / min, and then mixed evenly under the condition that the stirring rate is 11000 - 13000 r / min to obtain the cement slurry for resisting carbon dioxide corrosion.

[0041] Next, the technical solutions in the present invention will be described clearly and completely in conjunction with the embodiments in the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments in the present invention without creative efforts shall fall within the protection scope of the present invention.

[0042] In the examples and comparative examples: the salt content in water is 0.3 g / L; the cement is JiaHua G-class oil well cement, purchased from Sichuan JiaHua Cement Factory. The fluid loss reducer is SCF-180L, the dispersant is USZ, the retarder is SCR-6, and the defoamer is DZX-1, all from Dezhou Continental Shelf Petroleum Engineering Technology Co., Ltd.

[0043] Example 1

[0044] (1) Mix 60 g of nano-silica (particle size of 50 nm), 6 g of flaky graphene (thickness of 3 - 5 nm, average particle size of 0.2 - 1 μm), 5 g of sodium dodecyl sulfonate with 320 g of water, and perform ultrasonic treatment for 30 min to obtain a dispersion;

[0045] (2) Mix 32 g of fluid loss additive, 2 g of dispersant, 1 g of retarder, 5 g of defoamer with the above dispersion uniformly to obtain a mixed material liquid;

[0046] (3) At a stirring rate of 4000 r / min, add 800 g of cement to the above mixed material liquid. After the addition is completed, mix uniformly at a stirring rate of 12000 r / min to obtain a cement slurry resistant to carbon dioxide corrosion.

[0047] Example 2

[0048] (1) Mix 50 g of nano-silica (particle size of 50 nm), 10 g of flaky graphene (thickness of 3 - 5 nm, average particle size of 0.2 - 1 μm), 4 g of sodium dodecyl sulfonate with 360 g of water, and perform ultrasonic treatment for 30 min to obtain a dispersion;

[0049] (2) Mix 38 g of fluid loss additive, 3 g of dispersant, 2 g of retarder, 6 g of defoamer with the above dispersion uniformly to obtain a mixed material liquid;

[0050] (3) At a stirring rate of 4000 r / min, add 800 g of cement to the above mixed material liquid. After the addition is completed, mix uniformly at a stirring rate of 12000 r / min to obtain a cement slurry resistant to carbon dioxide corrosion.

[0051] Example 3

[0052] (1) Mix 70 g of nano-silica (particle size of 50 nm), 8 g of flaky graphene (thickness of 3 - 5 nm, average particle size of 0.2 - 1 μm), 6 g of sodium dodecyl sulfonate with 400 g of water, and perform ultrasonic treatment for 30 min to obtain a dispersion;

[0053] (2) Mix 35 g of fluid loss additive, 4 g of dispersant, 3 g of retarder, 4 g of defoamer with the above dispersion uniformly to obtain a mixed material liquid;

[0054] (3) At a stirring rate of 4000 r / min, add 800 g of cement to the above mixed material liquid. After the addition is completed, mix uniformly at a stirring rate of 12000 r / min to obtain a cement slurry resistant to carbon dioxide corrosion.

[0055] Example 4

[0056] (1) Mix 40 g of nano calcium carbonate (particle size of 100 nm), 3 g of flaky boron nitride (thickness < 100 nm, average particle size of 1 - 3 μm), 2 g of sodium glycocholate with 200 g of water, and perform ultrasonic treatment for 30 min to obtain a dispersion;

[0057] (2) Mix 45 g of fluid loss reducer, 1 g of dispersant, 4 g of retarder, 8 g of defoamer with the above dispersion evenly to obtain a mixed material liquid;

[0058] (3) At a stirring rate of 4000 r / min, add 800 g of cement to the above mixed material liquid. After the addition is completed, mix evenly at a stirring rate of 12000 r / min to obtain a cement slurry resistant to carbon dioxide corrosion.

[0059] Example 5

[0060] (1) Mix 80 g of nano titanium dioxide (particle size of 10 nm), 12 g of flaky boron nitride (thickness < 100 nm, average particle size of 1 - 3 μm), 8 g of polysorbate with 450 g of water, and perform ultrasonic treatment for 30 min to obtain a dispersion;

[0061] (2) Mix 25 g of fluid loss reducer, 5 g of dispersant, 0.5 g of retarder, 2 g of defoamer with the above dispersion evenly to obtain a mixed material liquid;

[0062] (3) At a stirring rate of 4000 r / min, add 800 g of cement to the above mixed material liquid. After the addition is completed, mix evenly at a stirring rate of 12000 r / min to obtain a cement slurry resistant to carbon dioxide corrosion.

[0063] Example 6

[0064] Same as Example 1, the difference is that the addition amount of the defoamer is 1 g.

[0065] Comparative Example 1

[0066] Same as Example 5, the difference is that the defoamer is omitted.

[0067] Comparative Example 2

[0068] Same as Example 5, the difference is that the flaky boron nitride is replaced with nano titanium dioxide in equal amount.

[0069] Comparative Example 3

[0070] Same as Example 5, the difference is that the nano titanium dioxide is replaced with flaky boron nitride in equal amount.

[0071] Test Example 1

[0072] Test the performance of the cement slurries prepared in the examples and comparative examples. The specific test methods are as follows:

[0073] The cement slurry was cured in a water bath curing kettle at 90°C for 21 days and then solidified into cement stone. It was then placed at 90°C, with a total pressure of 17MPa and a carbon dioxide partial pressure of 5MPa for 21 days for carbon dioxide corrosion treatment. The compressive strength of the cement stone before and after corrosion treatment was tested according to GB / T50081, and the permeability of the cement stone before and after corrosion treatment was tested according to SY / T5336 2006. The test results are shown in Table 1:

[0074] Table 1

[0075]

[0076] The cement stone formed after the cement slurry provided in the present invention is solidified has a compressive strength of not less than 30MPa after being treated with carbon dioxide corrosion at 90°C, and the decrease rate of the compressive strength before and after carbon dioxide corrosion does not exceed 15%. The permeability before and after carbon dioxide corrosion is not higher than 0.05 / mD. As shown in Table 1, the mechanical properties of the cement stone are stable under high temperature and high carbon dioxide environments, and the carbon dioxide corrosion resistance is excellent. Therefore, the cement slurry in the present invention can be used in oil and gas wells with high carbon dioxide, which can ensure the long-term sealing integrity of the cement ring in the presence of carbon dioxide, and can provide technical support for cementing operations in oil and gas wells containing acidic gas.

[0077] By comparing Example 1 and Example 6, it can be seen that, within the scope defined by the present invention, when the amount of surfactant added is the same, increasing the amount of defoamer used, the synergistic effect between the defoamer and the surfactant is stronger, which can further prevent the precipitation of solid particles, minimize the density difference between the upper and lower parts of the cement stone, avoid cracking of the cement stone due to poor local bearing capacity, and help improve the corrosion resistance and compressive strength of the cement stone.

[0078] By comparing Example 5 and Comparative Example 1, it can be seen that if the defoaming agent is omitted, more pore structures will exist in the formed cement stone, forming crossflow channels, which will significantly reduce the compressive strength and corrosion resistance and significantly increase the permeability.

[0079] By comparing Example 5 with Comparative Examples 2-3, it can be seen that compared with the use of flaky boron nitride alone or the use of nano-titanium dioxide alone, the synergistic effect of flaky boron nitride and nano-titanium dioxide can utilize the combination of shape and particle size to better fill the irregular pore structure in the cement stone, which is beneficial to improving the mechanical strength and corrosion resistance of the cement stone.

[0080] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited thereto. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solutions of the present invention, including the combination of each technical feature in any other suitable manner. These simple modifications and combinations should also be regarded as the content disclosed by the present invention and fall within the protection scope of the present invention.

Claims

1. A cement slurry resistant to carbon dioxide corrosion, characterized in that: The raw materials for preparing the cement slurry include, by weight: 800 parts of cement, 40-80 parts of nano-particle filler, 2-15 parts of flaky filler, 1-10 parts of surfactant, 1-8 parts of defoamer, 20-50 parts of fluid loss reducer, 0.5-5.5 parts of dispersant, 0.5-6.5 parts of retarder and 200-500 parts of water.

2. The cement slurry according to claim 1, wherein: The particle size of the nanoparticle filler is 1-100 nm, preferably 30-60 nm; Preferably, the thickness of the flake filler is 1-120 nm, preferably 1-50 nm; the average particle size is 0.1-10 μm, preferably 0.2-1 μm.

3. The cement slurry according to claim 1 or 2, wherein: The nanoparticle filler is selected from one or more of nano-silicon dioxide, nano-zirconium dioxide, nano-calcium carbonate, nano-titanium dioxide, and nano-zinc oxide, preferably nano-silicon dioxide; Preferably, the flaky filler is selected from one or more of flaky graphene, flaky boron nitride, flaky montmorillonite, and flaky molybdenum disulfide, preferably flaky graphene.

4. The cement slurry according to any one of claims 1 to 3, wherein: The surfactant is one or more of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium glycocholate, fatty acid glyceride, fatty acid sorbitan, polysorbate, preferably sodium dodecyl sulfonate.

5. The cement slurry according to any one of claims 1 to 4, wherein: The defoamer is a polyether defoamer.

6. The cement slurry according to any one of claims 1 to 5, wherein: The fluid loss reducer is selected from one or more of hydrolyzed polyacrylonitrile, carboxymethyl hydroxyethyl cellulose, and 2-acrylamide-2-methylpropanesulfonic acid-acrylic acid-acrylamide triblock copolymer, preferably 2-acrylamide-2-methylpropanesulfonic acid-acrylic acid-acrylamide triblock copolymer.

7. The cement slurry according to any one of claims 1 to 6, wherein: The dispersant is selected from one or more of formaldehyde acetone condensation polymer, styrene-maleic anhydride copolymer, and polynaphthalene sulfonate, and is preferably formaldehyde acetone condensation polymer.

8. The cement slurry according to any one of claims 1 to 7, wherein: The retarder is selected from one or more of sodium ethylenediaminetetramethylenephosphonate, sodium borate, and 2-acrylamide-2-methylpropanesulfonic acid / itaconic acid copolymer, preferably 2-acrylamide-2-methylpropanesulfonic acid / itaconic acid copolymer.

9. The cement slurry according to any one of claims 1 to 8, wherein: The salt content of the water is ≤0.5 g / L, preferably 0.2-0.5 g / L.

10. A method for preparing cement slurry according to any one of claims 1 to 9, wherein: The method comprises: mixing cement, nano-particle filler, flaky filler, surfactant, defoamer, fluid loss reducer, dispersant, retarder and water to obtain the cement slurry; Preferably, the method comprises the following steps: (1) uniformly mixing a nanoparticle filler, a flaky filler, a surfactant and water to obtain a dispersion; (2) uniformly mixing a fluid loss reducer, a dispersant, a retarder, and a defoamer with the dispersion to obtain a mixed liquid; (3) Add cement into the mixed liquid and mix them evenly to obtain the cement slurry resistant to carbon dioxide corrosion.